Factors Affecting The Efficiency And Effectiveness Of Pharmaceutical Inventory Control Of IVF Services Using The Minimum-Maximum Stock Level (MMSL) Method - Prasasya Paramesthi; Sutopo Patria Jati; Antono Suryoputro (Eduvest - Journal of Universal Studies, 2024)
Good control of the supply of drugs and consumables (BMHP) by Hospital Pharmaceutical Installations (IFRS) can avoid shortages or overstocks in pharmaceutical warehouses. The Type C "X" Special Hospital in Semarang City experienced a stockout of IVF drugs and embryo laboratory BMHP which resulted in delays in medical procedures and a decrease in the quality of service. The purpose of this study is to determine the factors that affect the efficiency and effectiveness of pharmaceutical preparations using the MMSL method. This study is a quasi-experimental non-equivalent without control group, samples were taken purposively using retrospective data from October – December 2023 with a stable supply and the research was applied prospectively from January – March 2024. Twelve types of IVF drugs and 56 types of BMHP embryo laboratories were used as research samples. The statistical test used cross-tabulation between efficiency variables (inventory value, inventory turnover ratio [ITOR], stockout value) and effectiveness (number of stockout events). The test results showed that the lower the price of IVF drugs and BMHP in embryo laboratories led to lower inventory values. The more expensive the BMHP price of embryo laboratories results in higher ITOR. The faster the lead time supplier BMHP embryo laboratory, the smaller the stockout will occur. The larger the Smin, Smax, and BMHP safety stock of the embryo laboratory, the lower the incidence of stockout. This study provides an insight into the factors that support the application of MMSL to inventory control in IFRS "X".